PSIX-28 The Effectiveness of the Parelli Horsenality Profiling System in Determining Suitability of Horses for Therapeutic Riding Programs. (7th December 2018) - Anderson, M; Ramagli, L; Beverly, M; Leatherwood, J
Abstract: When utilizing horses for therapy their individual disposition or "horsenality" leads to high burn out rates of horses in therapeutic riding programs. The Parelli Horsenality Profiling System may help remedy this, as it is a 100-question exam designed to determine the horsenality characteristics of a horse. Therefore, the objective of this study was to use the Parelli system to indicate which horsenality characteristics are most influential when identifying a suitable therapeutic riding horse. Horses (n=13) were evaluated for long term suitability as a therapeutic riding horse based on handler evaluation. The long-term tier scoring system used a scale ranging from one to four, with one being the most desirable horse for therapeutic riding and four being a horse that is undesirable for therapeutic riding. These scores were averaged from instructors (n=4) that have worked with the horses included in the study for over two years. In addition to long term assessment, each horse was evaluated on the Parelli system by the primary instructor of the facility. Once completed, all horsenality characteristics were run in a stepwise regression to predict long term suitability. From the stepwise regression, 8 of the 41 variables included in the analysis (age, bracy, tense, shy, non-responsive, buck/charge, pushy, and easily bored) were found to be significant in predicting long term suitability. Of these traits, age, bracy, tense, non-responsive, pushy, and easily bored had a positive relationship to long term suitability, indicating that horses prominently displaying these traits do not have long term success as a therapeutic riding horse. While the solution to this problem is in no way complete, using the Parelli system should give insight into the disposition of the horse, an therefore into its use in this growing field.